Comparison of Nasal Packing versus Septal Stitich on Airway Complications during Recovery from Anesthesia - Hayat, Muhammad Asif; Sabirdr, Ghulam; Hussain, Saddam; Shabbir, Afzal; Mehdi, Taffazul; Iqbal, Rashid (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare the incidence of airway related complications associated with nasal packing versus septal stitch in the post-operative period in patients presenting for elective septoplasty for deviated nasal septum (DNS).Study Design: Randomized controlled trial (Iranian registery of Clinical trials: 75068)Place and Duration of Study: Department of Anesthesia, Combined Military Hospital, Rawalpindi Pakistan, from Mar to Aug 2023.Methodology: Septoplasty was done under general anesthesia in both groups and before extubation, Group-N (n=110) received bilateral Vaseline soaked nasal packing and Group-S received quilted septal sutures (n=110). Primary variables studied were mean time from recovery room to discharge, mean dose of analgesia used post-procedure and pre-discharge, incidence of laryngospasm, hypoxia, bleeding, and headache in 6 hours in the immediate post-operative period in the pre-anesthesia care unit or in the ward.Results: Mean time from recovery to discharge being 19.19±2.24 hours in Group-N versus 12.32±1.36 hours in Group-S (p